DUAL BIOLOGICAL THERAPY IN INFLAMMATORY BOWEL DISEASE - Aleksandra Karnas; Gabriela Majka; Karol Bednarz; Piotr Pitrus; Anita Krowiak; Magdalena Kowalczyk; Karolina Krowiak; Anita Warzocha; Wiktoria Hander; Maria Jasiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Background: Inflammatory bowel diseases are increasingly common conditions occurring mainly in young people. The etiology of these diseases is not fully understood, so the treatment of choice is mainly conservative. The main target is to achieve and sustain clinical and endoscopic glucocorticosteroid-free remission. Purpose: The purpose of this study is to describe the non-standard use of dual biological therapy in selected groups of patients who have lost secondary response to treatment. Description: This article discusses two cases of patients suffering from ulcerative colitis and Crohn’s disease. During standard therapy, disease exacerbations and secondary loss of response to biologic drugs were observed. The combination of two biologic drugs resulted in remission of the disease and improvement in the patient’s clinical condition. Conclusions: Dual biologic therapy may show promise in the treatment of inflammatory bowel disease in selected groups of patients. Combining different mechanisms of action of drugs allows for comprehensive control of inflammation, increasing the effectiveness of treatment.